Book review: Zegart, Amy B. Spies, lies, and algorithms: the history and future of American intelligence - Elena Maceviciute (Information Research: An International Electronic Journal)
Zegart, Amy B. Spies, lies, and algorithms: the history and future of American intelligence. Princeton, NJ: Princeton University Press, 2023. xviii, 414 p. ISBN 978-0-691-22307-0